Gastrointestinal stromal tumor presenting as an ovarian malignancy: an unusual report of a case diagnosed on histopathology and immunohistochemistry - Bushra; Sabina Khan; Shaan Khetrapal; Durre Aden; Soumya Tiwari; Sujata Jetley (MGM Journal of Medical Sciences)
Gastrointestinal stromal tumors (GISTs) are the most prevalent malignant tumors of mesenchymal origin. They typically express the KIT receptor tyrosine kinase, which plays a key role in their pathogenesis. Mutations in the KIT gene often result in continuous activation of this receptor, leading to uncontrolled cell proliferation and resistance to apoptosis. Clinically, GISTs may imitate gynecological tumors during physical examination and pelvic ultrasound, making diagnosis challenging due to their nonspecific features and similarity to gynecologic malignancies. A 44-year-old female patient presenting with features of perforation peritonitis and a free-floating large pelvic mass mimicking gynecologic origin highlights the diagnostic difficulty posed by such cases. Ongoing research is needed to assess the diagnostic value of CD117-negative but DOG1-positive immunomarkers in identifying these tumors. Accurate diagnosis of GISTs, especially when they occur alongside other malignancies, requires a thorough clinical assessment, detailed immunophenotypic profiling, and advanced imaging techniques.